Therapeutic Potential of Human Adipose-Derived Stem/Stromal Cell Microspheroids Prepared by Three-Dimensional Culture in Non-Cross-Linked Hyaluronic Acid Gel. (22nd October 2015) - Mineda, Kazuhide; Feng, Jingwei; Ishimine, Hisako; Takada, Hitomi; Doi, Kentaro; Kuno, Shinichiro; Kinoshita, Kahori; Kanayama, Koji; Kato, Harunosuke; Mashiko, Takanobu; Hashimoto, Ichiro; Nakanishi, Hideki; et al.
Abstract : Human adipose-derived stem/stromal cell spheroids enriched in undifferentiated cells were efficiently prepared by using three-dimensional floating culture in non-cross-linked hyaluronic acid gel. The results suggest the superior plasticity and growth factor-secreting potential of the spheroids and clearly indicate their therapeutic power for promoting tissue regeneration. As an easy local injectable, spheroids are expected to be a powerful tool to treat various stem cell-depleted conditions/organs through nonintravenous administration. Abstract: : Three-dimensional culture of mesenchymal stem/stromal cells for spheroid formation is known to enhance their therapeutic potential for regenerative medicine. Spheroids were prepared by culturing human adipose-derived stem/stromal cells (hASCs) in a non-cross-linked hyaluronic acid (HA) gel and compared with dissociated hASCs and hASC spheroids prepared using a nonadherent dish. Preliminary experiments indicated that a 4% HA gel was the most appropriate for forming hASC spheroids with a relatively consistent size (20–50 µm) within 48 hours. Prepared spheroids were positive for pluripotency markers (NANOG, OCT3/4, and SOX-2), and 40% of the cells were SSEA-3-positive, a marker of the multilineage differentiating stress enduring or Muse cell. In contrast with dissociated ASCs, increased secretion of cytokines such as hepatocyte growth factor was detected in ASC spheroids cultured under hypoxia. On microarray ASC spheroids showed upregulation of some pluripotency markers and downregulation of genes related to the mitotic cell cycle. After ischemia-reperfusion injury to the fat pad in SCID mice, local injection of hASC spheroids promoted tissue repair and reduced the final atrophy (1.6%) compared with that of dissociated hASCs (14.3%) or phosphate-buffered saline (20.3%). Part of the administered hASCs differentiated into vascular endothelial cells. ASC spheroids prepared in a HA gel contain undifferentiated cells with therapeutic potential to promote angiogenesis and tissue regeneration after damage. Significance: This study shows the therapeutic value of human adipose-derived stem cell spheroids prepared in hyarulonic acid gel. The spheroids have various benefits as an injectable cellular product and show therapeutic potential to the stem cell-depleted conditions such as diabetic chronic skin ulcer.